The right to abortion: a comparative study between penal code and syariah law / Rafika Shari'ah Mohd Hassan - Mohd Hassan, Rafika Shari'ah (2007)
The research is conducted to compare the legal rights of abortion specifically in the area of the rights conferred on woman to abort the pregnancy, the issue of illegal abortion and to determine the punishments for abortion from the Penal Code and the Syariah law. The research is also providing alternatives and suggestions to remedy abortion particularly the punishments for illegal abortion.